2011
DOI: 10.1504/ijogct.2011.043714
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of effects of oil shale composition on its calorific value and oil yield

Abstract: This paper reports results of a detailed geochemical analysis carried out on representative oil shale samples obtained from the Attarat Um Ghudrandeposit, in Jordan. The conducted tests aimed to determine main features of the studied samples, such as oil yield, calorific value, organic and inorganic composition and moisture content. Based on obtained results of a large number of oil shale samples, as received without any treatment, it was found that as other types of oil shale, elsewhere, Attarat Um Ghudran oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The results of this study are comparable with those reported by Shaker et al (2014), using different sampling strategies, stratigraphic horizons, and locations for these oil shale deposits. However, the study oil shale has a relatively loweryield of shale oil and gas, compared to other deposits in Jordan and the Dead Sea area, US Green River, and the Estonia (up to 250 l/ton shale oil yield), (e.g., Shirav (Schwartz) and Ginzburg, 1983;Jaber et al, 2011;Speight, 2012;Alnawafleh and Fraige, 2015).…”
Section: Fischer Assay Yieldmentioning
confidence: 87%
See 2 more Smart Citations
“…The results of this study are comparable with those reported by Shaker et al (2014), using different sampling strategies, stratigraphic horizons, and locations for these oil shale deposits. However, the study oil shale has a relatively loweryield of shale oil and gas, compared to other deposits in Jordan and the Dead Sea area, US Green River, and the Estonia (up to 250 l/ton shale oil yield), (e.g., Shirav (Schwartz) and Ginzburg, 1983;Jaber et al, 2011;Speight, 2012;Alnawafleh and Fraige, 2015).…”
Section: Fischer Assay Yieldmentioning
confidence: 87%
“…The average content of spent shale in the analyzed samples ranges between 81.7% and 92.2% by weight with an average of 89.8%, as shown in Table 1. Spent shale is the residual ash of the pyrolysis process, which is considered here mainly as a high carbonate-base spent shale (e.g., Jaber et al, 2011). The spent shale content is inversely related to the oil (Fig.…”
Section: Fischer Assay Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are vast proven reserves of oil shale of more than 70 billion tons, within an average content of shale oil, i.e. liquid fuel, yield between 5-8 billion ton [1,2]. In addition, Jordan has abundant supplies of RE sources: high average daily solar radiation of between 5-7 kWh m -2 day, and acceptable wind speed (6-8 m/s) to generate electricity [3].…”
Section: Introductionmentioning
confidence: 99%